Hydrogen Peroxide Producing Titania-Silica Supraparticles as Tailorable Photocatalysts for Flow Chemistry Reactions in Microfluidic Reactors - Herbig, Bettina; Cermjani, Egzon; Hanselmann, Doris; Schmitt, Angelika; Deckers, Christoph; Rehm, Thomas H.; Mandel, Karl; Wintzheimer, Susanne (Chem & Bio Engineering, 2025)
The development of hybrid catalysts for cascade reactions that demonstrate high efficiency and longevity strongly relies on the precise arrangement of the individual components within such a material. This guarantees both their proximity for enhanced interaction and, at the same time, sufficient separation avoiding mutual harm. Before the acutal design of a usually very complex hybrid catalyst, it is essential to study and understand the impact of structural characteristics on catalytic activities of each catalytically active constituent separately. This study thus focuses on a comprehensive structure-activity analysis of the component within a highly customizable TiO2-SiO2 material, which produces H2O2 photocatalytically. The tailorable design of the hybrid material is achieved through the utilization of the spray-drying process. The H2O2 productivity of the obtained so-called TiO2-SiO2 supraparticles is demonstrated in both a batch and a flow reactor, marking a crucial step toward their future application as hybrid catalysts in photoassisted cascade reactions.
CRIS-Team Scopus Importer:2025-04-04
Keywords: cascade reaction; flow chemistry; hydrogen peroxide production; microfluidic reactor; photocatalyst; Supraparticles; titania